Fuzzy-based NCTF control of PTP positioning system - Purtojo, Purtojo; Wahyudi, Martono; Akmeliawati, Rini; Shafie, Amir Akramin (2009)
Nominal characteristic trajectory following (NCTF) controller had been proposed as a practical control method of point-to-point (PTP) positioning systems. Basically the NCTF controller composes of two elements namely nominal characteristic trajectory (NCT) and a compensator. As the NCTF controller is designed based on a simple open loop response of the controlled-object, it leads to the ease of controller design and simplicity of the controller structure for practical application. Moreover, the NCTF controller also has capability to achieve high accuracy, fast response and robustness to plant uncertainties. However, the original NCTF controller uses a proportional+integral (PI) compensator which is designed without systematic procedure for obtaining the best PI compensator parameters. To overcome this problem, fuzzy compensator has been proposed. Although simulation studies show that the proposed fuzzy compensator performed better than the PI one, experimental works have to be done to evaluate the effectiveness of the proposed fuzzy controller in real-time applications. Hence, in this paper, experimental studies on the implementation of the fuzzy-based NCTF controller are carried out. The experimental results confirmed that not only in the simulation but also in the real-time implementation the proposed fuzzy compensator is effective to replace the use of the PI compensator.